Sexual Transmission of Hepatitis B virus: Epidemiological Considerations and Implications for Control with Vaccine - Franklyn N Judson (Canadian Journal of Infectious Diseases)
Prior to the acquired immune deficiency syndrome (AIDS) epidemic, more than 50% of the new hepatitis B virus infections in the United States and Canada were sexually transmitted, approximately one-quarter by heterosexual men and women and one-third by homosexual men. The percentage of hepatitis B virus infections attributable to heterosexual transmission in developing and developed countries of Asia is unknown, but is probably proportionate to the percentage of the population which escapes perinatal and early childhood infection. In homosexual men of developed countries, fear of AIDS has led to dramatic reductions in high risk sexual behaviour and hence in the incidence of hepatitis B virus infection. Specific interventions designed to prevent sexual transmission of human immunodeficiency virus (eg. testing for infection status and counselling, choosing partners carefully, avoiding prostitutes, use of condoms, and diagnostic and treatment services for other sexually transmitted diseases) should further reduce hepatitis B virus sexual transmission in men and women. Eventually, however, hepatitis B virus vaccination programs will need to be considered for all countries. They should take into account regional epidemiology, vaccination cost-benefit, and program goals such as prevention of perinatal infection, sexually transmitted acute hepatitis, and/or cirrhosis and hepatic cancer, as well as containment versus eradication of the virus. If eradication is the goal, the only valid strategy is universal vaccination of infants or young adolescents - or both.